A gene and its product required for transposition of resistance transposon Tn2603. - Tanaka, M (1982)
Tn2603 is a multiple-resistance transposon encoding resistance to ampicillin, streptomycin, sulfonamide, and mercury and having a molecular size of 20 kilobase pairs, with 200-base-pair inverted repeats at both ends. The essential sites and functions of Tn2603 which are required for its transposition were determined through construction and characterization of various deletion mutants affecting the efficiency of transposition. Deletions were introduced in plasmid pMK1::Tn2603 by partial digestion with restriction endonuclease EcoRI in vitro. Analysis of deletion mutants showed that the inverted repeat segments at both ends of the trans-acting diffusible product(s) encoded in the right-hand side of the central portion were required for the transposition of Tn2603. An essential gene product was revealed as a protein having a molecular weight of 110,000 by analysis of polypeptides synthesized in Escherichia coli minicells. This protein was assumed to be the so-called transposase.